Missing in action and lost in thought: a grassroots implementation of genre pedagogy by practitioner researchers in an English language classroom for adults - Scott, Andrew Glencairn; Hafenstein, Tanja (Signo, 2021)
This paper reports on the grass roots adoption of a methodology for teaching reading and writing based on genre theory (Martin and Rose, 2012; Rose and Martin, 2012) in English for general purposes classes at an English language teaching (ELT) centre at an Australian university. We report on teachers’ experiences on using genre pedagogy, informed and inspired by the Reading to Learn (R2L) program and genre pedagogy from the so-called ‘Sydney School’ (Martin & Rose, 2007; Martin & Rose, 2008; Rose & Martin, 2012). We report on how we introduced elements of the R2L program into our lessons using a ‘bottom up’ approach with the view that individual teachers might find this useful for implementation of this methodology in their own contexts. We found that genre pedagogy can be adopted by teachers and implemented at the classroom level despite such challenges as teachers learning new classroom practices and reconciling differences with previous classroom practices.